Local Kyai's Religious Elite Transformation and Governance Paradox: A Comparative Study of Indonesia and Iran - Radius Setiyawan; Waode Hamsiah; Holy Ichda Wahyuni; Syahrul Ramadhan; Eka Firmansyah (International Journal of Law and Society, 2026)
The intersection of religious authority and political power presents critical governance challenges in Muslim-majority societies, yet systematic comparative frameworks remain limited. This study examines the political agency of religious elites, kyais in Madura, Indonesia, and ulama in Iran, across two structurally distinct institutional contexts: a democratic-electoral system and a theocratic-constitutional system. Using a Most Different Systems Design (MDSD), this study treats religious elites as the primary unit of analysis, addressing cross-level comparability between Madura as a subnational region and Iran as a nation-state at the actor level rather than the systemic level. A qualitative comparative case study within an interpretivist-constructivist paradigm was employed, drawing on interviews, participant observation, FGDs, and document analysis across four regencies in Madura (November 2023–May 2024), supplemented by expert consultations for the Iranian context. Findings reveal two fundamentally divergent trajectories: Madura exhibits pragmatic-electoral engagement producing significant regional variation, while Iran demonstrates constitutional institutionalization through the Wilayat al-Faqih doctrine. Three distinct actor network configurations were identified: hierarchical-institutional (Iran), multipolar-informal (Bangkalan), and pluralistic-deliberative (Sumenep). Paradoxically, religious elite political engagement reinforces exclusive governance practices in both contexts, intensifying clientelism in Madura while generating complex dual accountability structures with limited public participation in Iran. This study proposes that governance quality under religious elite agency is mediated by institutionalization, ideological coherence, and actor network configuration, with direct relevance to SDG 16.